O Programa Nacional de Direitos Humanos e a promoção da cidadania no Brasil - Bombarda, Alex Ricardo [UNESP] (2015)
The objective of this work will be discuss about the Programa Nacional de Direitos Humanos (PNDH) analyzing, besides your importance for the promotion of human rights in Brazil, the propositions and measures, contained in PNDH-3, that it can be implemented. This research starts from the hypothesis that the issue of human rights is not a priority for most of the congressman. We will seek to show that set up the context of intense dispute. Besides your effectiveness, also will be verified the way how the particular interests overlaps in the collective order, by defacing the democratic principles present in the constitution of 1988. The study of Programa Nacional de Direitos Humanos is justified according as will allow to reflect about the context of the construct of human rights in Brazil, contributing for the studies of the formation of Brazilian citizenship. How about of the methodology, this project will bring, firstly, a bibliographical research about the thematic referred with the objective redeem the historical contexts that enabled the debate about the issue of the human rights in Brazil. Secondly, others source will be used for widen the understanding about the discussion that makes about of the human rights issues and justice in Brazil. By this bias, it will be considered the two newspaper's archive: O Estado de São Paulo and the Folha de São Paulo, made available on sites http://acervo.estadao.com.br/ and http://acervo.folha.com.br/. We used the keyword resource- PNDH, in this research- for the search files. The period that matches to the search is from 01/01/1995 until 05/30/2014. The purpose of this temporal cut is associated to the need seek get all the newspaper article and news reports published one year before of the first PNDH edition until the most recent period, for monitoring the measures of the programs that have been implemented. Besides the newspaper, it will be used too, to check the program proposals ...